Development of technology and investigation of structure and properties of composites on the basis of shungit and polymer resins; IOP Conference Series: Materials Science and Engineering; Vol. 81 : Radiation-Thermal Effects and Processes in Inorganic Materials - Kupchishin A. I. Anatoliy Ivanovich; Nauryzbaev M. K.; Kupchishin A. A.; Komarov F. F.; Remnev G. E. Gennady Efimovich; Voronova N. A.; Kaikanov M. I. Marat Islambekovich (2015, 2015)
Title screen